Skrining Fitokimia Senyawa Metabolit Sekunder dari Ekstrak Etanol Daun Gedi (Abelmoschus manihot L.) - Sari, Indri Novita; Parbuntari, Hesty (Lembaga Yasin AlSys, 2025)
Gedi leaves (Abelmoschus manihot L.) are known for their potential as a natural ingredient in the development of traditional medicines; however, information regarding their secondary metabolite content remains limited. This study aims to identify the secondary metabolites present in the ethanol extract of gedi leaves through phytochemical screening. The extraction was conducted using the maceration method with 96% ethanol on dried powdered gedi leaves. The resulting extract was qualitatively analyzed using specific reagents to detect compound groups such as alkaloids, flavonoids, saponins, steroids, and terpenoids. Compound detection was based on color changes as indicators of positive reactions. The screening results revealed the presence of alkaloids, flavonoids, and steroids, while saponins and terpenoids were not detected. These findings indicate that gedi leaves contain bioactive compounds that hold relevance for further development in pharmaceutical research. This study provides an initial contribution to the exploration of the pharmacological potential of A. manihot and supports future studies aimed at isolating and characterizing its active compounds in greater detail.